ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP PADA MATERI KESEBANGUNAN DENGAN MODEL PEMBELAJARAN PROBLEM SOLVING - Rahmawati, Fitriana (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This study aims to analyze and describe the problem-solving abilities of junior high school students on similarity material with the Problem Solving learning model. This research is a qualitative descriptive study. The subjects of this study were 27 children. Samples of class students at SMP Negeri 45 Bandar Lampung. The method used to collect data is to use written worksheets with mathematical problem solving skills on congruence material. The results showed that the mathematical problem solving abilities of class IX students of SMP Negeri 45 Bandar Lampung were already high. Judging from the presentation, it was stated that students were able to identify known elements, apply strategies and develop mathematical models. Overall, students' mathematical problem-solving abilities, especially in congruence material, are in high qualification, although there are some students who are still in low qualification.